2018
DOI: 10.4269/ajtmh.17-0583
|View full text |Cite
|
Sign up to set email alerts
|

Serial Measurements of Soap Weights and Soap Availability to Describe Handwashing Behavior

Abstract: Available measures of handwashing are prone to bias. We tested the feasibility and reliability of weighing soap at repeated visits and subtracting the measured weight from the prior weight to assess daily per capita soap consumption in a low-income community in Dhaka, Bangladesh. Fieldworkers approached 220 households twice weekly over 2 months. They interviewed participants, weighed soap, and assessed hand cleanliness and the presence of a handwashing station. Respondents used bar soap (91% [201]) and laundry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…There were household land uses in the three samples, as shown in Figure 1. However, the average household consumption of detergent cake was only 3.2 g per person per day (Gadgil et al, 2018). The result of low detergent concentration indicated that only a small amount of detergent content is wasted on surface water bodies.…”
Section: Detergentmentioning
confidence: 98%
“…There were household land uses in the three samples, as shown in Figure 1. However, the average household consumption of detergent cake was only 3.2 g per person per day (Gadgil et al, 2018). The result of low detergent concentration indicated that only a small amount of detergent content is wasted on surface water bodies.…”
Section: Detergentmentioning
confidence: 98%